The Merits of Pooling Claims Revisited - Gatzert, Nadine; Schmeiser, Hato (The Journal of Risk Finance, 2012)
Purpose Definitions of pooling effects in insurance companies may convey the impression that the achieved risk reduction effect will be beneficial for policyholders, since typically lower premiums are paid for the same safety level with an increasing number of insureds, or a higher safety level is achieved for a given premium level for all pool members. However, this view is misleading and the purpose of this paper is to reexamine this apparent merit of pooling from the policyholder's perspective. Design/methodology/approach This is achieved by comparing several valuation approaches for the policyholders' claims using different assumptions of the individual policyholder's ability to replicate the contract's cash flows and claims. Findings The paper shows that the two considered definitions of risk pooling do not offer insight into the question of whether pooling is actually beneficial for policyholders. Originality/value The paper contributes to the literature by extending and combining previous work, focusing on the merits of pooling claims (using the two definitions above) from the policyholder's perspective using different valuation approaches.
WiSo-Import:2015-03-26:3054
Keywords: Theory of Risk; Risk Valuation; Risk Pooling